INVESTIGATION OF THE PANDEMIC PREPAREDNESS EDUCATION OF CRITICAL CARE NURSES - Alduraywish, Thamer; West, Sandra; Currie, Jane (LIFE: International Journal of Health and Life-Sciences, 2019)
Critical care nurses play important roles in the secondary level management and prevention of communicable disease during a pandemic. These roles include leading the pandemic response, efficiently managing limited resources, instituting infection control, and providing safe and effective care. Nurses face many challenges in adequately performing their roles given the complexity of a pandemic. Therefore, nurses must possess the relevant skills and knowledge to competently execute their tasks. This study aims to identify the research evidence underpinning the knowledge and skills required for critical care nurses to respond to a pandemic as described. An Integrative review (IR) was used and employing studies that used different research designs. As a result, a total of 33 studies were identified; qualitative (n = 17), quantitative (n = 11), and mixed-method studies (n= 5) were retrieved for the review. Emerging themes include staff attitudes and ethics, organisation, planning, and education.In conclusion critical care nurses need specialised pandemic response education to meet the challenges of managing and preventing disease outbreaks. Hospital planners and educators will benefit from improving institutional pandemic plans to build staff capacity through education and training. However, there is still a need for developing evidence-based curriculum for nursing pandemic preparedness.